Affecting Factors on Social Problem-Solving Ability of University Students (Medico Legal Update, 2019)
Background/Objectives: This study is a descriptive research to identify the factors influencing university students’ ability to solve social problems.Method/Statistical analysis: From November 18 to December 16, 2017, 250 university students in Korea were surveyed and data was collected. Data was pulled from 213 questionnaires as 37 questionnaires were inappropriately responded. SPSS Win 22.0 Program was used for data analysis.Findings: The social problem-solving ability of university students showed a positive correlation with social support (r = .377, p